The demand for euro area currencies: past, present and future - Björn Fischer; Petra Köhler; Franz Seitz (European Central Bank (ECB), 2004)
The present paper analyses currency in circulation in the euro area since the beginning of the 1980s. After a comprehensive literature review on this topic we present some stylised facts on currency holdings in the euro area countries as well as at an aggregate euro area level. The next chapter develops a theoretical model, which extends traditional money demand models to also incorporate arguments for the informal economy and foreign demand for specific currencies. In the empirical sections we first estimate the demand for euro legacy currencies in total and for small and large denominations within a cointegration framework. We find significant differences between the determinants of holdings of small and large denominations as well as overall currency demand. While small-value banknotes are mainly driven by domestic transactions, the demand for large-value banknotes depends on a short-term interest rate, the exchange rate of the euro as a proxy for foreign demand and inflation variability. Large-value banknotes seem to be therefore used to an important extent as a store of value domestically and abroad. As monetary policy is mainly interested in getting information on the demand for currency used for domestic transactions we also try several approaches in this direction. All the methods applied result in rather low levels of transaction balances used within the euro area of around 25% to 35% of total currency. After this we deal with possibly changing cost-benefit-considerations of the use of cash due to the introduction of euro notes and coins. Overall, there seems no evidence so far of a substantial decline of the demand for currency in the euro area.
Keywords: E41; E52; E58; 330; cointegration; currency in circulation; purposes of holding currency